Atrial Fibrillation and Myocardial Infarction: A Systematic Review and Appraisal of Pathophysiologic Mechanisms. Issue 5 (20th May 2016) - Violi, Francesco; Soliman, Elsayed Z.; Pignatelli, Pasquale; Pastori, Daniele
Abstract : Background: A growing body of evidence suggests that atrial fibrillation (AF) is associated with myocardial infarction (MI). However, incidence and management of MI in AF is still undefined. Methods and Results: We searched MEDLINE via PubMed and Cochrane database between 1965 and 2015. All observational clinical studies and interventional trials reporting 1‐year incidence of MI in AF were included. We also discussed pathophysiological mechanisms, predictors, and therapeutic approaches to reduce the risk of MI in AF. Twenty‐one observational studies and 10 clinical trials were included. The annual rate of MI in observational studies including AF patients ranged from 0.4% to 2.5%. Higher rates of MI were reported in AF patients with stable coronary artery disease (11.5%/year), vascular disease (4.47%/year), heart failure (2.9%/year), and in those undergoing coronary artery interventions (6.3%/year). However, lower annual rates have been described in AF patients from Eastern countries (0.2–0.3%/year), and in those enrolled in clinical trials (from 0.4 to 1.3%/year). Conclusions: AF patients had a significant residual risk of MI despite anticoagulant treatment. Coexistence of atherosclerotic risk factors and platelet activation account for the increased risk of MI in AF. Identification of high‐risk AF patients is a needed first step to develop cost‐effective approaches for prevention. A new score, the 2MACE score, has been recently developed to stratify MI risk in AF, and may help not only in allocating resources to high‐risk groups, but also in design of studies examining novel therapies for prevention of MI in AF.